Wall Street :how it works and for whom - Henwood, Doug (Verso, 1997)
With compelling clarity, Henwood dissects the world's greatest financial center, laying open the Intricacies of how, and for whom, the market works. The Wall Street which emerges is not a pretty sight. Hidden from public view, the markets are poorly regulated, badly managed, chronically myopic and often corrupt. And though, as Henwood reveals, their activity contributes almost nothing to the real economy where goods are made and jobs created, they nevertheless wield enormous power.